IMPLEMENTASI KURIKULUM PEMBELAJARAN MANDIRI MELALUI PROGRAM PENGEMBANGAN KEPROFESIAN GURU - Yasa Stapa (Jurnal Literasi Pendidikan Dasar, 2023)
This study aims to investigate the effectiveness of teacher professionalism training and development programs in implementing the independent learning curriculum at MIN units in Labuan Bajo. The research questions focus on the impact of such programs on teachers' attitudes, knowledge, and practices, as well as the extent to which these programs improve the implementation of independent learning. A mixed-methods approach will be employed, consisting of surveys, interviews, and observations. The collected data will be analyzed through both descriptive and inferential statistics to identify any significant differences in teacher performance before and after participating in the training programs. The study's findings are expected to contribute to effectiveness of teacher professionalism training and development programs in enhancing the implementation of independent learning curriculums, particularly at MIN units in Labuan Bajo.